Options for Increased Private Sector Participation in Resilience Investment : Focus on Agriculture - Tordo, Silvana; Lorenzato, Gianni; Zhao, Jing; McEneaney, Kyle; Sarmiento-Saher, Sebastian Phillip (World Bank, Washington, DC, 2018)
The presence of a revenue stream and a commercial return are an absolute prerequisite for investment for the private sector. However, often adaptation benefits or the value added (resilience) of adaptation investment are difficult to quantify in financial terms. There is no accepted methodology to price the adaptation feature of an investment, that is to quantify whenan investment has successfully adapted to climate change. While the risks from extreme weatherand climate change are clearly recognizable, and many investors see these risks in the present ornear term, uncertainty about the precise nature, timing and severity of climate impacts makes the return on investment of adaptation projects difficult to measure. In many cases adaptation is embedded into project design and engineering. The fact that the adaptation component is often not able to be separated, or treated as an add-on feature, has consequences for fund raising and project financing. Particularly for infrastructure projects, the difficulty in ring-fencing adaptation components, and the uncertainty around the time and magnitude of climate impacts, make it difficult to charge separate/properly priced tariffs. These difficulties are compounded in emerging and developing economies (EMDEs), where users’ ability to pay is limited. Blended finance solutions are used to make projects bankable by closing viability gaps. Blended finance consists in the complementary use of concessional (grants or low interest instruments) and non-concessional financing from public and private sources to make projects financially viable and/or financially sustainable. Applying this approach to climate finance allows leveraging of limited public funding, enhances the overall effectiveness of aid, and potentially triggers an increase in private investment once the long-term viability of a market is demonstrated. This report analyzes the potential and need for blended finance solutions in four economic sectors - water, agriculture, transport, and energy. For each economic sector, two broad classes of investment, infrastructure and value chains, are discussed. Investing in infrastructure or in value chains (that is, the range of goods and services that link the producer to the customers or end-consumer) requires different competencies, investment processes, project selection criteria, and attracts different classes of investors. Each investment theme is assessed for its resilience relevance and potential for commercial returns. An in-depth analysis of financing needs and potential blended finance solutions for resilience investment in the agriculture sector is presented, because of the economic relevance of agriculture in EMDEs, and its exposure to climate and natural hazards.